Radical Sacrifice : The Rise and Ruin of Fitz John Porter - Marvel, William (Book collections on Project MUSE., 2021)
"Radical Sacrifice chronicles the life and military career of Union general Fitz John Porter, commander of the Army of the Potomac's Fifth Corps under George McClellan. A highly ranked graduate of the United States Military Academy, Porter rose steadily through the ranks during the Mexican-American War and subsequent military action in the West. With the outbreak of the Civil War, Porter became a favorite of McClellan, distinguishing himself in several key battles during 1862. But when fellow Union generals John Pope and Irvin McDowell accused him of costing the Union the battle of Second Bull Run (August 1862), Porter was court-martialed and dismissed for disobedience and misconduct before the enemy. To this day, it is generally accepted that a self-serving cabal of officers and government officials (including Judge Advocate Joseph Holt and Secretary of War Stanton) wrongly convicted Porter because he was a Democrat rather than a committed supporter of Lincoln. As such, he found himself on the wrong side of debates regarding the purpose of the Union's struggle, making him the perfect scapegoat. Not until 1879 was Porter able to clear his name and have the court martial reversed. Even still, his reputation remains tarnished to the present day"--